Surface chemistry gradients on silicone elastomers for high‐throughput modulation of cell‐adhesive interfaces. Issue 6 (18th October 2014) - Mohan, Greeshma; Gallant, Nathan D.
Abstract Combinatorial and high‐throughput approaches to screening cell responses to material properties accelerate the speed of discovery and facilitate the identification of cell instructive cues or trends that may be missed by discrete sampling. However, these technologies have not yet been widely applied to materials with tissue‐like stiffness. The fabrication of monotonically varying surface chemistry gradients on polydimethylsiloxane, an elastic biomaterial, and the influence of these engineered surfaces on protein adsorption and adherent cell morphology were explored in this study. Crosslinked networks of polydimethylsiloxane were functionalized with a hydrophobic self‐assembled monolayer and then modified by spatiotemporally regulated ultraviolet ozonolysis to obtain gradients of oxygenated species ranging from ∼10° to ∼100° in water contact angle. Automated microscopy and image analysis of fibroblast cell morphology revealed a strong correlation between cell spreading and hydrophobicity. However, structural and functional analysis of the fibronectin interface indicated a proportional increase in cell spreading with adsorption, but a biphasic relationship with fibronectin conformation, underscoring the complexity of the adhesive interface. This work demonstrates the development of an elastomer surface modification platform that can be extended to future combinatorial studies of biological responses to chemical and mechanical material properties. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 2066–2076, 2015.